2021
DOI: 10.1088/1755-1315/718/1/012037
|View full text |Cite
|
Sign up to set email alerts
|

Hatching and harvesting techniques for Artemia cysts with different effects of salinity in the district of Situbondo, East Java

Abstract: Artemia sp. is a natural food that is very important in the hatchery of marine fish, crustaceans, freshwater fish consumption and ornamental fish. This happens because Artemia has a high nutritional value and the size that matches the mouth opening of almost all types of fish larvae. Artemia can be applied in a variety of fish and shrimp hatcheries. Good seawater, brackish and fresh. The advantage of Artemia compared to other natural foods in aquaculture is that they are traded in the form of cysts, so they ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 1 publication
2
9
0
1
Order By: Relevance
“…In accordance with previous studies, extreme salinities (low or high) and low temperatures are observed to inhibit Artemia hatching verifying the existence of optimal hatching conditions (Ahmed et al, 1997; Bahr et al, 2021; Hasan and Rabbane, 2018; Kumar and Babu, 2015; Sharahi and Zarei, 2016; Wasonga and Olendi, 2018). However, while these previous studies primarily focus on endpoint measurements of the hatching rate, here we have established relationships between the hatching rate and the progression of hatching and respiration behavior throughout the process.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In accordance with previous studies, extreme salinities (low or high) and low temperatures are observed to inhibit Artemia hatching verifying the existence of optimal hatching conditions (Ahmed et al, 1997; Bahr et al, 2021; Hasan and Rabbane, 2018; Kumar and Babu, 2015; Sharahi and Zarei, 2016; Wasonga and Olendi, 2018). However, while these previous studies primarily focus on endpoint measurements of the hatching rate, here we have established relationships between the hatching rate and the progression of hatching and respiration behavior throughout the process.…”
Section: Discussionsupporting
confidence: 90%
“…Ahmed et al reported that the optimal salinity for hatchability is 20 ppt (Ahmed et al, 1997). In another study done by Bahr et al on the influence of salinity on hatching, the optimal hatchability was found at salinities of 60 ppt and temperatures around 30°C (Bahr et al, 2021). The variation in optimal parameters could be due to differences in test settings (e.g., light exposure (Arun et al, 2017; Asil et al, 2023; Sharahi and Zarei, 2016)) or variance in environmental conditions (container size, temperature/salinity gradients in bulk media).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ahmed et al reported that the optimal salinity for hatchability is 20 ppt 31 . In another study done by Bahr et al on the influence of salinity on hatching, the optimal hatchability was found at salinities of 60 ppt and temperatures around 30 °C 28 . The variation in optimal parameters could be due to differences in test settings (e.g., light exposure 25 , 30 , 32 ) or variance in environmental conditions (container size, temperature/salinity gradients in bulk media).…”
Section: Introductionmentioning
confidence: 89%
“…al., 2017; Orire & Nwafor, 2008;Bahr et al, 2021). When testing with a wide range in hatching success.…”
mentioning
confidence: 99%